Key questions in applied ecology and conservation a study and revision guide - Rees, Paul A. (CAB International, 2021)
"An understanding of applied ecology and conservation is an important requirement of a wide range of programmes of study including applied biology, ecology, environmental science and wildlife conservation. This book is a study and revision guide for students following such programmes. It contains 600 multiple-choice questions (and answers) set at three levels - foundation, intermediate and advanced - and grouped into 10 major topic areas: History and foundations of applied ecology and conservation Environmental pollution and perturbations Wildlife and conservation biology Restoration biology and habitat management Agriculture, forestry and fisheries management Pest, weed and disease management Urban ecology and waste management Global environmental change Environmental and wildlife law and policy Environmental assessment, monitoring and modelling The book has been produced in a convenient format so that it can be used at any time in any place. It allows the reader to learn and revise the meaning of terms used in applied ecology and conservation, study the effects of pollution on ecosystems, the management, conservation and restoration of wildlife populations and habitats, urban ecology, global environmental change, environment law and much more. The structure of the book allows the study of one topic area at a time, progressing through simple questions to those that are more demanding. Many of the questions require students to use their knowledge to interpret information provided in the form of graphs, data or photographs
Keywords: Ökologie; Applied ecology; Wildlife conservation; Lehrbuch